2013
DOI: 10.1074/jbc.m112.410233
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-20 Promotes Migration of Bladder Cancer Cells through Extracellular Signal-regulated Kinase (ERK)-mediated MMP-9 Protein Expression Leading to Nuclear Factor (NF-κB) Activation by Inducing the Up-regulation of p21WAF1 Protein Expression *

Abstract: Background:The role of in tumor migration remains to be elucidated. Results: IL-20 induces cell migration via ERK1/2-mediated NF-B/MMP-9 regulation by inducing p21 WAF1 expression. Conclusion: p21WAF1 is essential for the cell migration induced by IL-20. Significance: This work provides novel insights into the molecular events of IL-20-mediated cancer cell migration indicating it is dependent on p21 WAF1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 43 publications
4
113
0
Order By: Relevance
“…IL-20 promotes angiogenesis in vitro and in vivo by inducing migration of endothelial cells and promoting vascular endothelial growth factor (15). IL-20 has also been reported to increase MMP-9 expression (20).…”
Section: Discussionmentioning
confidence: 99%
“…IL-20 promotes angiogenesis in vitro and in vivo by inducing migration of endothelial cells and promoting vascular endothelial growth factor (15). IL-20 has also been reported to increase MMP-9 expression (20).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that JNK1/2 and ERK1/2 transcriptionally regulate the expression of MMP-2 and MMP-9, which results in regulation of cell migration and invasion (25)(26)(27). In human bladder cancer cells, upregulation of the MAPK pathways may result in migration and regulation of the expression levels of MMPs (28). Furthermore, it has been reported that decreased phosphorylation of ERK1/2 and JNK may be involved in regulation of bladder cancer cell migration (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways induce MMP-9 expression, particularly the p38 MAPK, JNK, and ERK pathways [31, 32]. α-mangostin inhibits the expression of MMP-2 and MMP-9 via inhibition of JNK phosphorylation, and thereby suppresses the migration and invasion of PC-3 prostate cancer cells [20], and it also inhibits ERK signaling pathways in HCT-116 colorectal carcinoma cells [33] and pancreatic cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%